The effect of Sape' music therapy and endorphin massage on labor pain in Mempawah Regency in 2025 - Yuni Rosanti; Putri Azzahroh; Bunga Tiara Carolin (Rajaki of Tulip Medika Publisher, 2026)
Background: Labor pain can cause anxiety and fatigue, which may affect the progress of labor and fetal well-being. One approach to managing labor pain is through non-pharmacological methods, such as endorphin massage and instrumental music therapy, specifically sape music. Objective: To analyze the effect of endorphin massage and sape music therapy on labor pain before and after treatment in Mempawah Regency. Methods: This study employed a quasi-experimental design with a pretest– posttest nonequivalent control group design. The study population consisted of women in the active phase of the first stage of labor from August to October 2025, totaling 97 individuals. A total of 30 participants were selected, consisting of 15 participants in the intervention group who received endorphin massage combined with sape music therapy and 15 participants in the control group. The sampling technique used was consecutive sampling. Results: The mean labor pain score before and after the administration of Sape's music therapy and endorphin massage in the intervention group decreased from 6.33 to 4.67, while in the control group, it decreased from 6.33 to 4.66. There was a significant effect of Sape's music therapy and endorphin massage on labor pain (p-value < 0.001). There was no significant difference in the mean pain scores between the intervention and control groups (p = 1,000). However, after treatment, the mean labor pain score in the intervention group was lower than that in the control group (p=0.039). Conclusion: Endorphin massage combined with sape ' music therapy was more effective than endorphin massage alone, with a mean difference of 1.000 in the endorphin massage and sape ' music therapy group and 0.039 in the endorphin massage-only group. Recommendation: It is recommended that endorphin massage and sape music therapy be applied as alternative non-pharmacological methods for managing labor pain and further developed in future studies with larger sample sizes.